2021
DOI: 10.1039/d1ra02573b
|View full text |Cite
|
Sign up to set email alerts
|

Electroactive macromolecular motors as model materials of ectotherm muscles

Abstract: Macromolecular motors from model materials of ectotherm muscles work as electro-chemo-mechanical and thermo-mechanical transducers harvesting, above 35 °C, up to 60% of the reaction energy from the thermal environment saving chemical energy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 137 publications
(203 reference statements)
0
12
0
Order By: Relevance
“…Entry and expulsion of the solvent ions from and to the electrolyte for the osmotic pressure balance was responsible for the conformational change. 29 A small open portion was observed on the left side of the QV response which represented the charge consumption for an irreversible reaction that occurred parallel to the reduction of the film. The irreversible charge consumption was due to the hydrogen gas evolution at the interface of the Pt/film.…”
Section: Co-operative Actuation Studies -Voltammetric Responses Drive...mentioning
confidence: 99%
See 3 more Smart Citations
“…Entry and expulsion of the solvent ions from and to the electrolyte for the osmotic pressure balance was responsible for the conformational change. 29 A small open portion was observed on the left side of the QV response which represented the charge consumption for an irreversible reaction that occurred parallel to the reduction of the film. The irreversible charge consumption was due to the hydrogen gas evolution at the interface of the Pt/film.…”
Section: Co-operative Actuation Studies -Voltammetric Responses Drive...mentioning
confidence: 99%
“…The compositiondependent properties of CPs pertaining to their electrochemical characteristics can be tuned to design sensing motors capable of sensing their own working conditions without additional connectivity just as biological muscles do. 29 When wet, CPs can be considered as reactive gels capable of responding to external stimuli. Their composition changes in a reversible and controlled manner, driven by a reversible redox process accompanied by changes in volume, conductivity, colour, shape, and/or charge storage.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 17 The electrochemical reactions that generate the movement, more precisely the ionic exchange between the liquid electrolyte and the PPy film emerging from applying a current/potential can be influenced by numerous parameters. It was reported that PPy based bilayer and trilayer actuators can also be used as physical (mechanical 18 or tactile 19 , 20 ) or chemical (current, concentration, temperature, electrolyte type 21 , 22 ) sensors. Although some progress in developing intrinsically sensing artificial muscles has been made, improvements are still needed for obtaining more reactive, highly sensitive devices suited for applications.…”
Section: Introductionmentioning
confidence: 99%